Types of common errors in Middle Eastern students’ opinion essays: A case study - Suriya Kumar, Sinnadurai; Hafizoah, Kassim; Nursyaheedah, Muhammad Isa; Fathiah Izzati, Mohammad Fadzillah; Nurkarimah, Yusof; Nik Aloesnita, Nik Mohd Alwi (UiTM, 2019)
Analyzing students’ written errors is an approach to better understand the challenges that second and especially foreign language learners faced while writing in English. The aim of this study is to investigate the common errors in English essays made by English as a foreign language learners focusing on students from the Middle Eastern countries. Participants were ten male students who attended a preparatory intensive English program at a public university, and they were required to write an opinion essay at the beginning of the program. The errors were analyzed, identified and categorized using the parameter of types of errors set by Carl James, i.e. general grammatical, substance, lexical, syntactic and semantic errors. The findings showed that students made all types of errors with a heavy percentage on general grammatical, substance and syntactic errors. It was also found that some students did not adhere to the standard structure of an essay. By identifying the common errors, it has become an essential strategy to assist teachers to understand students’ weaknesses in writing, and their needs in order to prepare appropriate strategies and learning materials to help the students.